Climate-responsive Social Protection - Kuriakose, Anne T.; Heltberg, Rasmus; Wiseman, William; Costella, Cecilia; Cipryk, Rachel; Cornelius, Sabine (World Bank, Washington, DC, 2013)
In the years ahead, development efforts aiming at reducing vulnerability will increasingly have to factor in climate change, and social protection is no exception. This paper sets out the case for climate?responsive social protection and proposes a framework with principles, design features, and functions that would help Social Protection (SP) systems evolve in a climate?responsive direction. The principles comprise climate?aware planning; livelihood?based approaches that consider the full range of assets and institutions available to households and communities; and aiming for resilient communities by planning for the long term. Four design features that can help achieve this are: scalable and flexible programs that can increase coverage in response to climate disasters; climate?responsive targeting systems; investments in livelihoods that build community and household resilience; and promotion of better climate risk management.